Tantangan demokrasi Pancasila di era digital: Menganalisis dampak penyebaran hoaks, disinformasi, dan polarisasi di media sosial terhadap nilai-nilai Pancasila seperti persatuan dan keadilan sosial - anggraini, sabrina irma (Maliki Interdisciplinary Journal, 2025)
The challenges to Pancasila Democracy in the digital era: Analyzing the impact of the spread of hoaxes, disinformation, and polarization on social media on Pancasila values such as unity and social justice. The development of information and communication technology has drastically changed human interaction, giving rise to ethical and legal challenges such as hoaxes, disinformation, hate speech, and polarization on social media. In the Indonesian context, these digital issues threaten the nation's ideological foundation, Pancasila, especially the values of humanity, unity, and social justice. The spread of hoaxes and disinformation can damage public trust in democratic institutions, while opinion polarization causes social fragmentation that erodes social cohesion and national unity. Social media algorithms exacerbate the circulation of hoaxes and deepen polarization by creating filter bubbles. Therefore, Pancasila has a strategic role as a moral guide and public ethics in the digital world. This study aims to analyze the relationship between Pancasila morality and contemporary digital challenges, and to actualize Pancasila's values of humanity, unity, and social justice in the protection of digital rights and the development of an ethical, safe, and just digital space. Systematic steps are needed, including strengthening regulations, instilling Pancasila-based digital literacy, and multi-stakeholder collaboration to maintain information integrity and strengthen national unity.